2018
DOI: 10.1002/cbf.3357
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 Tat‐induced bystander apoptosis in Jurkat cells involves unfolded protein responses

Abstract: The HIV transactivator protein (Tat) is a multifunctional protein that plays a critical role in viral replication and contributes to several pathological symptoms of HIV‐1 infection, which has the loss of CD4+ T lymphocytes as one of its hallmark features. It has been shown that endoplasmic reticulum (ER) stress, including viral infections, is implicated in cellular dysfunction and cell death through activation of the unfolded protein response (UPR). Here, we demonstrate that the bystander stimulus of Tat on J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 53 publications
1
18
1
Order By: Relevance
“…It was observed that Tat remained near to the mitochondria [ 57 , 58 ], suggesting cellular distribution is related to organelle alterations. Accordingly, other findings revealed that Tat-exposed cells present mtDNA damage [ 20 , 59 ] and alteration in its methylation patterns [ 60 ], mitochondrial membrane potential reduction [ 23 ] changes in size and morphology of the organelle, fusion-fission triggering [ 24 ], increased mitochondrial ROS [ 61 , 62 ], mitophagy disruption [ 17 , 57 ], mitochondrial functions dysregulation [ 17 , 61 ] calcium homeostasis disturbance [ 61 , 63 , 64 ], and apoptosis activation [ 23 , 58 , 61 , 65 , 66 ].…”
Section: Tat and Mitochondriamentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that Tat remained near to the mitochondria [ 57 , 58 ], suggesting cellular distribution is related to organelle alterations. Accordingly, other findings revealed that Tat-exposed cells present mtDNA damage [ 20 , 59 ] and alteration in its methylation patterns [ 60 ], mitochondrial membrane potential reduction [ 23 ] changes in size and morphology of the organelle, fusion-fission triggering [ 24 ], increased mitochondrial ROS [ 61 , 62 ], mitophagy disruption [ 17 , 57 ], mitochondrial functions dysregulation [ 17 , 61 ] calcium homeostasis disturbance [ 61 , 63 , 64 ], and apoptosis activation [ 23 , 58 , 61 , 65 , 66 ].…”
Section: Tat and Mitochondriamentioning
confidence: 99%
“…The reported data shows that Tat-exposed cells undergo extrinsic [ 65 ] and intrinsic apoptosis pathways [ 23 ]. In the first one, the signaling process starts in the cell membrane and is triggered by stimulation of death receptors, followed by activation of caspases to initiate cell death.…”
Section: Tat and Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies from our lab demonstrate induction of the three UPR pathways in primary human astrocytes in response to HAND-relevant stimuli (whole HIV-1, inflammation, and ART drugs), which associate with mitochondrial depolarization ( Nooka and Ghorpade, 2017 ). HIV-1 Tat-induced ER stress in a CD4+ T cell line ( Campestrini et al, 2018 ) neurons ( Norman et al, 2008 ) and human brain microvascular endothelial cells (HBMEC) ( Ma et al, 2016 ) are also accompanied by changes in mitochondrial function and apoptotic signaling supporting cooperation of the ER and mitochondria during HIV/HAND pathology. Indeed, inhibition of ER stress reversed HIV-1-induced mitochondrial dysfunction and increased cell viability in HBMEC ( Ma et al, 2016 ).…”
Section: Human Immunodeficiency Virus- Associated Neurocognitive Disordersmentioning
confidence: 99%
“…This would prevent dead-end entry into doomed hosts, which are incapable of supporting productive infection. For example, HIV and SIV replicate primarily in a setting of increased uninfected CD4 + lymphocyte proliferation and turnover, marked by activation-induced cell death due to Fas and other contact-triggered suicide initiators, including uninfected cell contact with infected cells (13,30,51,57,60,64,87). Most leukocytes die within 12 h of initiating programmed cell death in vitro, and cell machinery required for viral integration, replication, assembly, and budding is compromised much sooner (23).…”
mentioning
confidence: 99%